2020
DOI: 10.3390/microorganisms8050624
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and Genetic Diversity of Primate Cytomegaloviruses

Abstract: Cytomegaloviruses (CMVs) infect many mammals, including humans and non–human primates (NHPs). Human cytomegalovirus (HCMV) is an important opportunistic pathogen among immunocompromised patients and represents the most common infectious cause of birth defects. HCMV possesses a large genome and very high genetic diversity. NHP–infecting CMVs share with HCMV a similar genomic organization and coding content, as well as the course of viral infection. Recent technological advances have allowed the sequencing of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 104 publications
(207 reference statements)
3
17
0
1
Order By: Relevance
“…Recently, several studies have reported on HCMV sequence information derived from comprehensive analyses using clinically relevant HCMVs as well as reference and laboratory strains [ 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. In order to collect more information about strain sequence variation of isolates in our present study, we performed viral whole genome sequencing (WGS) and comparative analysis of clinical isolates of HCMV.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, several studies have reported on HCMV sequence information derived from comprehensive analyses using clinically relevant HCMVs as well as reference and laboratory strains [ 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. In order to collect more information about strain sequence variation of isolates in our present study, we performed viral whole genome sequencing (WGS) and comparative analysis of clinical isolates of HCMV.…”
Section: Resultsmentioning
confidence: 99%
“…Herpesvirus infection, in particular, is a common concern during hematopoietic cell (and solid organ) transplant, where immunosuppression provides a cellular environment promoting viral infection and/or reactivation, which in turn can lead to additional myelosuppression, which can ultimately result in graft failure ( Ivana et al., 2022 ). Yet, while many mammalian species, from elephants to mice, are infected with herpesviruses, the evolutionary differences that prevent cross-infection, even between highly related primate betaherpesvirus species, highlight specific adaptations to the host immune system and distinct mechanisms of viral behavior ( Cagliani et al., 2020 ; Fisher and Lloyd, 2020 ). Understanding these mechanisms will provide novel insights into viral infection (and treatment), immune function, and hematopoietic mechanisms.…”
Section: Human Hematopoietic Hierarchy and Functionmentioning
confidence: 99%
“…Таким образом, геномы ЦМВ относительно пластичны и разнообразны с точки зрения содержания генов как на межвидовом, так и на внутривидовом уровне. Такая генетическая изменчивость в сочетании с иммунологической мимикрией, скорее всего, является ключевым элементом, лежащим в основе строгой видовой специфичности этих вирусов, а также их способности сохраняться на протяжении всей жизни с минимальными клиническими проявлениями [27]. В то же время при сравнении геномных последовательностей штаммов ЦМВ становится очевидным чрезвычайно высокий уровень их вариабельности, что объясняет сложность создания анти-ЦМВ-вакцины.…”
Section: цитомегаловирусная инфекцияunclassified